Simulation of a Cashless Future Economy: Implications for Monetary Stability and Financial Inclusion - Aulia Nur Azizah (PT. Anagata Sembagi Education, 2025)
This study analyzes the impact of the transition to a cashless economy on monetary stability and financial inclusion. Using a quantitative approach with secondary data analysis from 81 countries, the study evaluates the nonlinear relationship between financial inclusion and financial stability. The results indicate that the elimination of cash could enhance financial inclusion through digital technologies, but it also poses risks to monetary stability, particularly in countries with large informal sectors. A U-shaped relationship between financial inclusion and financial stability is observed, where early-stage inclusion stabilizes the financial system, but excessive inclusion without proper regulation can create new risks. Fintech technology plays a positive role in promoting inclusion with limited short-term risks to stability. The main barriers to financial inclusion include low financial literacy, high costs, lack of identity documents, and gender barriers. Effective solutions include service digitalization, financial education, and cross-sector collaboration. This study contributes to understanding the complex trade-off between stability and inclusion in the context of a digital economy.